(untitled) (Scientific journal of the Fergana State University, 2023)
Phonopoetics is one of the areas requiring special study within the framework of linguistic and poetic research. The fact that almost every linguopoetical research conducted in recent years, in one sense or another, includes phonopoetical analysis, indicates that phonopoetics is an integral part of linguopoetical research and a separate area of ​​research. The phonopoetic means used in the artistic image in accordance with the content and rhythm of the poem have a strong impact on the reader’s feelings. The connotative meaning of the word has the characteristic of stepping with the help of phonetic means. In this article, the skill of writing more than one vowel or consonant in a literary text, that is, the skill of using phonographic techniques, was subjected to linguo-poetic analysis. Object of study: the text of the poetic eras of A. Abidjan. Subject of study: linguistic and poetic features of phonographic units in the text of a work of art. Research method: system-structural analysis of language level units. On the example of the poetry of A. Abidjon, which is the object of this study, the author’s ability to use phonographic techniques is investigated.